2018
DOI: 10.1200/jco.2018.36.6_suppl.411
|View full text |Cite
|
Sign up to set email alerts
|

Erdafitinib (ERDA; JNJ-42756493), a pan-fibroblast growth factor receptor (FGFR) inhibitor, in patients (pts) with metastatic or unresectable urothelial carcinoma (mUC) and FGFR alterations (FGFRa): Phase 2 continuous versus intermittent dosing.

Abstract: 411 Background: Although immune checkpoint inhibitors (ICI) have improved outcomes in some pts with platinum-resistant mUC, many pts (eg, pts with TCGA luminal 1 tumors, many of whom are FGFRa) may not benefit. ERDA, a pan-FGFR (1-4) inhibitor, demonstrated promising phase 1 activity: 11 partial responses among 24 FGFRa mUC pts. We report efficacy and safety of ERDA in the ongoing global open-label phase 2 study BLC2001 (NCT02365597). Methods: Pts had measurable mUC with specific FGFR2/ FGFR3 mutations or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…For example, clinical tumor genomic profiling can prospectively identify potential therapeutic targets and thus guide treatment selection (28). Overall, over half of the urothelial tumors in the current study as well as the TCGA had potentially actionable genomic alterations, including ERBB2 amplifications and mutations and FGFR3 hotspot mutations (29). Furthermore, patients with Lynch syndrome are at increased risk for the development of UTUC, and the identification of patients with Lynch syndrome-associated tumors has treatment and screening implications for both affected patients and unaffected family members (30).…”
Section: Discussionmentioning
confidence: 88%
“…For example, clinical tumor genomic profiling can prospectively identify potential therapeutic targets and thus guide treatment selection (28). Overall, over half of the urothelial tumors in the current study as well as the TCGA had potentially actionable genomic alterations, including ERBB2 amplifications and mutations and FGFR3 hotspot mutations (29). Furthermore, patients with Lynch syndrome are at increased risk for the development of UTUC, and the identification of patients with Lynch syndrome-associated tumors has treatment and screening implications for both affected patients and unaffected family members (30).…”
Section: Discussionmentioning
confidence: 88%
“…160 The overall response rate was 42% in 59 patients for whom data were available. 160 Erdafitinib is also under investigation in the NCI-MATCH trial as a treatment for patients with tumors that have an FGFR mutation, fusion, or amplification (Table 7).…”
Section: Fgfr and Erdafitinibmentioning
confidence: 97%
“…Earlier this year, the FDA granted Breakthrough Therapy Designation for erdafitinib in the treatment of urothelial cancer, which is based on data from a multicenter phase 2 clinical trial focused on evaluating the efficacy and safety of erdafitinib in the treatment of adult patients with locally advanced or metastatic urothelial cancer harboring specific FGFR mutations . The overall response rate was 42% in 59 patients for whom data were available . Erdafitinib is also under investigation in the NCI‐MATCH trial as a treatment for patients with tumors that have an FGFR mutation, fusion, or amplification (Table 7).…”
Section: Other Hot Markers In Researchmentioning
confidence: 99%
“…In the first‐in‐human phase 1 study (EDI1001‐ [NCT01703481]), erdafitinib 9 mg once‐daily and erdafitinib 10 mg on a 7‐days‐on/7‐days‐off schedule demonstrated a manageable safety profile and achieved exposures resulting in clinical response, as measured by relative change from baseline in target lesion size . Recently, in a multicenter, open‐label, phase 2 study (BLC2001 [NCT02365597]), erdafitinib demonstrated efficacy and safety in adult patients with locally advanced or metastatic urothelial cancer, whose tumors harbor certain FGFR genetic alterations . Based on this evidence, erdafitinib was granted accelerated approval by the US Food and Drug Administration for the treatment of adult patients with locally advanced or metastatic urothelial carcinoma that has susceptible FGFR3 or FGFR2 genetic alterations and progressed during or following at least 1 line of prior platinum‐containing chemotherapy including within 12 months of neoadjuvant or adjuvant platinum‐containing chemotherapy .…”
mentioning
confidence: 99%
“…2 Recently, in a multicenter, open-label, phase 2 study (BLC2001 [NCT02365597]), erdafitinib demonstrated efficacy and safety in adult patients with locally advanced or metastatic urothelial cancer, whose tumors harbor certain FGFR genetic alterations. 3,4 Based on this evidence, erdafitinib was granted accelerated approval by the US Food and Drug Administration for the treatment of adult patients with locally advanced or metastatic urothelial carcinoma that has susceptible FGFR3 or FGFR2 genetic alterations and progressed during or following at least 1 line of prior platinum-containing chemotherapy including within 12 months of neoadjuvant or adjuvant platinum-containing chemotherapy. 5 Erdafitinib dose is individually titrated based on serum phosphate concentrations, a target engagement biomarker that reflects the extent of erdafitinib FGFR inhibition, and is expected to be linked to efficacy and safety outcomes.…”
mentioning
confidence: 99%